The Influence Of Leadership And Compensation On The Performance Of Employees In Cooperative Branch Office - Daniel Saut Halomoan; Ibnu Haris Nasution (SEAN Institute, 2023)
This study was to determine the effect of Leadership, Compensation, and Employee Performance at the Efraim Jaya Savings and Loan Business branch office company. In research using primary data. Sampling in this study used simple random sampling using predetermined criteria. The sample was selected from 54 employees. The analysis technique used in this research is SPSS (Statistical Product and Service Solution) version 26. The results of the study show that leadership has a significant effect positive and significant on employee performance, compensation has a significant effect positive and significant to employee performance R-square value of 0.732, meaning that the magnitude of the coefficient of determination is 0.732. This states that the independent variable can explain the dependent variable by 73.2% and the remaining 26.8% is influenced by other independent variables outside of this study.